2020
DOI: 10.47602/jpsp.v4i2.228
|View full text |Cite
|
Sign up to set email alerts
|

The Gratitude visit: Student reflections on a positive psychology experiential learning exercise

Abstract: This study aimed to examine students' subjective experiences and insights in response to engaging in a positive psychology exercise focused on gratefulness that was part of a college course. We conducted a qualitative content analysis of 97 reflection assignments submitted as part of undergraduate and graduate level positive psychology courses at a large public university. A grounded theory approach to qualitative research guided the analytic process. Six major themes emerged, including students’ thoughts abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Participants appreciated the added element of receiving a dose of gratitude from their recipients! The positive and meaningful qualitative results found in the current study are similar to those that emerged from Payne et al (2020), most notably, positive impacts on relationships and benefits on their own well-being as well as experiences of uncomfortable emotions related to the exercise. The quantitative results unique to this study add to Payne et al (2020) by suggesting increases in scores on measures assessing meaning in life, satisfaction with life, and happiness related to participation in the gratitude visit exercise.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Participants appreciated the added element of receiving a dose of gratitude from their recipients! The positive and meaningful qualitative results found in the current study are similar to those that emerged from Payne et al (2020), most notably, positive impacts on relationships and benefits on their own well-being as well as experiences of uncomfortable emotions related to the exercise. The quantitative results unique to this study add to Payne et al (2020) by suggesting increases in scores on measures assessing meaning in life, satisfaction with life, and happiness related to participation in the gratitude visit exercise.…”
Section: Discussionsupporting
confidence: 81%
“…These qualitative data highlight the positive effects of a gratitude visit intervention, while also noting some of the challenges of engaging with this exercise. This study noted the eagerness of students to meaningfully engage with positive psychology interventions through courses and encouraged the use of similar exercises in future courses (Payne et al, 2020).…”
Section: Gratitude Visits: Evidence Of Effectivenessmentioning
confidence: 90%
See 1 more Smart Citation
“…The study sample consisted of students assigned to engage in and think critically about positive psychology interventions. As reported in Payne et al (2020), in addition to writing one's obituary following a fruitful and satisfying life (Vail et al, 2012), students took note of things they were grateful for (Emmons & McCullough, 2003;Seligman et al, 2005), practiced giving active and constructive responses (Passmore & Oades, 2014), performed acts that were philanthropic and pleasurable (Otake et al, 2006), practiced savoring (Jose et al, 2012), identified and reflected upon character strengths (Seligman et al, 2005), and made a "gratitude visit" wherein Payne et al 100 they wrote and delivered a letter to someone whom they had not formally thanked (Kumar & Epley, 2018;Seligman et al, 2005). Assignments from students in six undergraduate courses (five of which were honors-level courses) and one graduate-level course (N = 109) were included.…”
supporting
confidence: 54%
“…The experiential learning model that has been applied so far has several weaknesses. According to previous study the experiential learning model has weaknesses in terms of participation in the industrial world and the world of work (Mc Pherson-Geyser et al, 2020;Nguyen, 2022). The learning experiences that have been provided to students so far have come entirely from the teacher, not the needs of the industrial world.…”
Section: Introductionmentioning
confidence: 99%